2010
DOI: 10.3141/2198-08
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Safety Prediction Methodology for Urban Signalized Intersections

Abstract: A coordinated effort is under way to develop a Highway Safety Manual (HSM) for use in making quantitative estimates of the safety performance of specific highway types and quantitative estimates of proposed improvements to specific highway types. The highway types being addressed in the first edition of HSM are rural two-lane highways, rural multilane highways, and urban and suburban arterials. Explicit consideration of pedestrian safety on urban and suburban arterials is considered critical to implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 5 publications
2
14
0
5
Order By: Relevance
“…Torbic et al combined databases from Toronto and Charlotte, North Carolina, that were used to develop SPFs for the first edition of the Highway Safety Manual and found that AADT and annual average daily pedestrians (AADP) are significant factors at threeto four-leg signalized intersections (5). Other significant predictors included maximum number of lanes crossed by a pedestrian in any one crossing maneuver, presence of bus stops, average neighborhood income, and number of commercial structures.…”
Section: Previous Studies and Context Of This Workmentioning
confidence: 99%
“…Torbic et al combined databases from Toronto and Charlotte, North Carolina, that were used to develop SPFs for the first edition of the Highway Safety Manual and found that AADT and annual average daily pedestrians (AADP) are significant factors at threeto four-leg signalized intersections (5). Other significant predictors included maximum number of lanes crossed by a pedestrian in any one crossing maneuver, presence of bus stops, average neighborhood income, and number of commercial structures.…”
Section: Previous Studies and Context Of This Workmentioning
confidence: 99%
“…The study suggested developing special leg form impactors for different countries with different average person height. A methodology was developed to quantify pedestrian safety effects related to existing site characteristics on urban and suburban arterials [12]. The study revealed that vehicle-pedestrian crash frequency was highest when the ratio of minor road AADT to major road AADT was the highest.…”
Section: Related Workmentioning
confidence: 99%
“…Tout d'abord, la largeur et le nombre de voies à traverser pour le piéton sont des éléments reconnus pour leur impact sur le risque : plus ce nombre est important, plus le temps d'exposition du piéton sur la chaussée est grand et plus il y a de risque de collision [19,20]. Torbic et al [21] ont aussi confirmé que la fréquence de collisions entre une voiture et un piéton est plus élevée aux carrefours ayant un plus grand nombre de voies à traverser. Des analyses récentes effectuées à Montréal ont confirmé cette tendance puisque Morency et al [22] ont démontré que la largeur de la route, la longueur de la traverse piétonne et le nombre de voies de circulation sont associés au nombre moyen de piétons blessés aux carrefours.…”
Section: Facteurs De Risque Environnementaux : Le Cas Des Piétons Danunclassified